A post COVID lockdown pilot study on the effect of physical activity intensity on cognitive functions of children aged 6-8 years old - Russo, G.; Castagnoli, M. S.; Babini, A.; Ceciliani, A. (Journal of Human Sport & Exercise, 2020)
Physical activity practice is very important for individual`s wealth status. Moreover, it is possible to consider physical activity one of the teachers` tool to improve the academic achievement and the cognitive functions in children. However, according to some evidences it seems that the physical activity at high intensity increase the cognitive functions compared to the low intensity physical activity. In this project, we investigate how the intensity of physical activity affects a series of cognitive functions such as Attention and Working Memory. Eleven participants of a summer camp participated at the study. Three experimental weeks with different physical intensities were involved (Standard Intensity, High intensity and Low Intensity). Participants performed the cognitive tasks at the beginning and at the end of each experimental week. Our results indicated an effect of the physical activity intensity in some kind of attention. Working Memory instead, was not affected. Thus, our results suggested that intensity could be an important factor to increase some cognitive functions, but not all of them.